International management : - McFarlin, Dean B. (Routledge, 2011)
The book gives students a global perspective on the process of hiring, training, and developing employees, as well as strategic decision making in relation to foreign markets. Questions, case studies, examples of creative problem solving, and testimonials from real-world managers operating in the international arena are just a few of the tactics McFarlin and Sweeney use to help students begin to think about applied theory on a global level. All chapters have been updated with recent articles from leading business sources and academic journals, and new case studies have been incorporated.